Techniques and procedures for the creation of Stop Motion products at national level: a bibliographic revision - Silva Bolívar, Juliana
This review article´s objective is to condense the knowledge obtained, in bibliographic reviews and the development experiences of own stop-motion products. For the analysis of the information, consider: stop motion audiovisual products published in Colombia, international referents productions in the industry, making off, degree theses, pedagogical material, articles and books. This allowed to acquire the necessary concepts to start the investigation. With the evolution of the audiovisual industry in recent years, more high-quality products are being generated every day. However, the budget remains being one of the drawbacks for innovation in this field. For this reason, the products that are offered locally maintain the same formats, because they are practical in their cost-benefit relationship. The competition increase in the audiovisual industry has been permanent, and to achieve a positioning of the national production it is necessary to find a differentiating factor, in which new formats based on new methodologies are implemented, capable of putting Colombia in a competitive position in the international market. This is achieved by executing projects planned to maximize quality at minimum cost, taking aesthetics into account as the fundamental essence of artistic direction and public demand.